IN-DEPTH LEARNING TRAINING AT UPTD. SDN 22 SAMPEAN - Salman Thoat; Zainal Efendi Hasibuan; Amron Hasibuan (PT. Jurnal Center Indonesia Publisher, 2026)
Deep learning is an important approach to improving the quality of 21st-century learning, but its implementation in elementary schools still faces various challenges, particularly related to teacher readiness and competency. This study aims to analyze the implementation and outcomes of deep learning training for teachers at the UPTD SDN 22 Sampean. The study used a qualitative approach with a field study design. The subjects were elementary school teachers who participated in the deep learning training. Data were collected through observation, interviews, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results of the study indicate that immersive learning training improved teachers' conceptual understanding and practical skills in developing immersive learning-based teaching materials. Teachers began designing lessons oriented toward conceptual understanding, active student engagement, and reflection on learning. These findings indicate that practice-based training is effective in supporting the implementation of immersive learning in elementary schools. This study recommends the need for ongoing training and implementation support to ensure the sustainability of immersive learning in the classroom.